Dermatiti occupazionali: problematiche gestionali. Nove anni di esperienza / Management of occupational dermatitis. Nine years’ experience - Crippa, M.; Paitoni, P.; Andreoli et al., D.M. (La Medicina del Lavoro, 2011)
«Management of occupational dermatitis. Nine years’ experience». Background: Dermatitis is a major problem in occupational medicine. Objectives: To evaluate management problems concerning 301 workers with occupational dermatitis (OD) referred to the Occupational Health Institute of Brescia in the period 2000-2008. Methods: We considered gender, age, job, referring physicians, diagnosis, latency between the onset of symptoms and the etiological diagnosis, examinations and tests performed before referral to our Institute. Results: We diagnosed 168 cases of allergic contact dermatitis, 101 cases of irritant contact dermatitis and 32 other forms of dermatitis. 51.8% of the workers had been referred by general practitioners and 45.9% by occupational physicians. The mean latency between onset of symptoms and etiological diagnosis was 36 months and was significantly longer for construction workers (60 months). General practitioners referred workers to dermatologists or allergists and prescribed appropriate treatment more frequently than occupational physicians. We performed specific allergological tests in 292 workers (97%): in 48 subjects the correlation between symptoms and occupational exposure was unclear and was verified more than once, in 29 workers we requested a dermatological consultation due to severe skin lesions. Frequently it was necessary to collect further detailed information on occupational exposure, thereby postponing the diagnosis by about 3-10 weeks. Conclusions: Management of OD is still not satisfactory due to inadequate information to workers on occupational risks, limited presence of occupational physicians in the workplaces, low quality health surveillance, underestimation of occupational risks by general practitioners who are frequently the main referents for workers, poor collaboration between all physicians involved in OD management.